Tindak Pidana Kelalaian Menyebabkan Luka yang Dilakukan oleh Dokter Gigi: Analisis Putusan Nomor: 257/Pid.B/2015/PN.Dps - Selly Ismi Qomariyah; Y.A Triana Ohoiwutun; Sapti Prihatmini (Lentera Hukum, 2018)
There is a substantial difference between the ordinary crime related to its results and that related to its causes. In order to classified as a crime, the negligence carried out by medical personnel needs to be previously described regarding the fulfillment of the elements of lawlessness. This paper analyzes whether there is medical malpractice and with the following lawlessness in the court decision number 257/Pid.B/2015/PN.Dps. Throughout the analysis, it will provide a comprehension to the qualification of whether malpractice, medical negligence or medical risk. The result of the study finds that such a crime can be qualified to medical malpractice, even though he did not fulfill the nature against formal law but it meets the element of nature against material law. Keywords: Medical Malpractice, Lawlessness, Crime